CPC-029 Characterization of Patients Non-Adherent to Highly Active Antiretroviral Therapy (HAART) Between 2010–2011. (12th March 2013) - Alcobia, A; Martins, M; Bravo, R; Leandro, A; Duarte, H; Santos, P; Lopes, A; Aragão, F
Abstract : Background: Thanks to the introduction of Highly Active Antiretroviral Therapy (HAART), a decrease has been observed in the number of hospital admissions, the incidence of opportunistic infections and mortality associated with HIV/AIDS. However, adherence to treatment continues to play a crucial role. In fact, a failure of HAART often leads to changes in laboratory parameters, development of resistant strains and the need to change treatment regimens. This study aims to analyse the impact of the failure of treatment changes on laboratory parameters and treatment regimens. Purpose: To characterise patients who had been included in the government's subsidised programme who were later excluded by their inability to follow treatment. Materials and Methods: Retrospective observational study. 50 patients, who had been taking HAART since January 2007 and abandoned it between January 2010 and December 2011, were randomly selected and analysed. The control group consisted of 50 adherent patients who began taking HAART since January 2007. Results: Preliminary data indicate that our patients are mainly male with a median age range of 40 years old. There was a need to change the treatment regimen in 83% of the patients due to their inability to follow treatment correctly. Even though the viral load was undetectable in 54% of the patients, 70% couldn't achieve a CD4 count above 350 cells/µL. The main reasons for the lack of adherence are drug and/or alcohol addiction (38%), distance to the hospital (13%), psychological causes (13%), adverse drug reactions (13%) and unknown reasons (25%). Conclusions: The patients' inability to follow HAART correctly often leads to the need to change the treatment regimen. Considering the present data, it's extremely relevant to characterise the non-adherent population, in order to improve adherence to HAART. No conflict of interest.